Influência espectral de telas de sombreamento na pós-colheita de alpínias - Maia, Mariane Oliveira (2015)
The manipulation of the intensity and spectral quality of the solar radiation in plant growing is done by using neutral or color shading nets. Although it can cause changes in plant development, it is not known the effect on post harvest quality when these shade cloths are used. Thus, the objective was to evaluate the effects of nets of different shading levels and spectral quality in alpinias 'Jungle King' and 'Jungle Queen' post-harvest quality. Flower stems stemmed crop under black shade cloths, with 30% and 50% shading, and blue and red nets with 50% of shading were maintained at the ambient temperature of 23°C for 15 days. The experimental design was distributed in a completely randomized way, totaling eight treatments of 4 replicates and two flower stems per plot. Evaluations of water uptake, relative fresh weight and quality through a scale of notes given by three evaluators were performed every two days, while reviews of the color of the bracts brightness parameters, chroma and Hue angle were performed every 3 days. Concurrently, bracts were collected every 3 days for the biochemical analysis of the activity of peroxidase and polyphenoloxidase. It was observed that the spectral quality influences the postharvest quality, and for the development and longevity of alpinia 'Jungle King' flower stems, blue and black 50% shading nets are more suitable, and for 'Jungle Queen', red nets. Stems stemmed from black shade cloth with 30% shading have a lower quality and post-harvest durability.